Meeting the Challenges of Health Transition in the Middle East and North Africa : Building Partnerships for Results - Time for Strategic Action - World Bank (Washington, DC, 2013)
In its recent history, the Middle East and North Africa region has made a remarkable progress in expanding access to basic health services for its citizens, and the Region can be justifiably proud of having achieved one of the fastest rates of decline in child mortality among all the developing regions of the world. These accomplishments are particularly noteworthy in that the Region maintained a steady mortality decline despite of the periods of stagnation in economic growth that have affected different parts of the Region over this period. They reflect the benefits of past investments in basic health services and the beneficiary effects of the broader social and economic development, such as improved access to safe drinking water and hygiene as well as the higher educational attainment of girls - all of which are known to have a positive impact on child and maternal health. These past achievements form an important basis for addressing future challenges. At the same time, the benefits of economic development are bringing new risks and health issues that will require substantial realignment of the existing policies and programs. Middle East and North Africa region has one of the youngest populations in the world; this provides a window of demographic opportunity to prepare the next generation of children and youth for a healthy and productive adulthood, and avoid the unnecessary suffering and heavy cost of modern diseases. The healthcare system will also need to be prepared to provide adequate financial protection and quality healthcare as the ageing population will require increasing support to avoid premature deaths and minimize the suffering from disabilities associated with chronic diseases and injuries.